Efisiensi Pengelolaan Keuangan dalam Meningkatkan Optimalisasi Fasilitas dan Jasa Pada Kantor Unit Penyelenggara Pelabuhan Kelas III Jailolo - Kurnia Kurnia (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the extent to which the Jailolo Class III Port Operator Office Unit manages the port facilities that have been built by the government in order to improve services that can contribute to the State treasury as well as convenience for service users using qualitative research methods. improve facilities and services at the port. To improve the optimization of facilities and improvements, it is necessary to repair and add supporting facilities. From the results of this study, it is known that in carrying out the duties and functions of the Jailolo Class III Port Management Unit Office in accordance with the regulations of Law Number 17 of 2008 concerning Shipping, it is clear that one task of the port office is to provide crossing facilities and provide a sense of security and comfort for users of transportation services. in this case sea transportation. These facilities are financed by the central government using APBN funds which are distributed to each regional satker every fiscal year. The port facilities in question are port supporting facilities, all of which are built and maintained by the Port Office as a mandate from the Central Government. All the facilities built are expected to provide an increase in revenue for the government in the form of PNBP (Non-Tax State Income) which can later be reused for port needs, both in developing existing facilities or for the construction of new facilities to increase port productivity.